2004
DOI: 10.1530/eje.0.1500323
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the human vitamin D receptor is associated with muscle strength, fat mass and body weight in Swedish women

Abstract: Objective: Bone mineral density (BMD) is under strong genetic control and a number of candidate genes have been associated with BMD. Both muscle strength and body weight are considered to be important predictors of BMD but far less is known about the genes affecting muscle strength and fat mass. The purpose of this study was to investigate the poly adenosine (A) repeat and the BsmI SNP in the vitamin D receptor (VDR) in relation to muscle strength and body composition in healthy women. Design: A population-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 21 publications
5
87
2
6
Order By: Relevance
“…Such difference, if present, would lead to a difference in functional response of muscle to vitamin D and therefore a difference in lean mass between VDR genotypes. There was no relationship between VDR polymorphisms and lean mass in either gender or age group in this study, similarly to what was found in previous studies (Grundberg et al, 2004;Garnero et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such difference, if present, would lead to a difference in functional response of muscle to vitamin D and therefore a difference in lean mass between VDR genotypes. There was no relationship between VDR polymorphisms and lean mass in either gender or age group in this study, similarly to what was found in previous studies (Grundberg et al, 2004;Garnero et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies assessed the relationship between VDR genotypes and muscle strength and/or lean mass in humans (Guesens et al, 1997;Pottelbergh et al, 2002;Grundberg et al, 2004), and between VDR and PTH levels (McClure et al, 1997;Pottelbergh et al, 2002;Zofkova et al, 2003;Macdonald et al, 2006). The expression of VDR in muscle decreases significantly with aging (Bischoff-Ferrari et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…More defined phenotypes have been proposed for studying obesity, such as fat mass, lean mass, and percentage fat mass. Genetic variation in VDR is associated with muscle strength, fat mass, and body weight in Swedish women [3] . Recently, however, Moreno et al [41] failed to find an association between VDR genotypes and haplotypes with fat-free mass in postmenopausal Brazilian women.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may correspondingly lead to osteoporosis and obesity. Both bone mass and obesity phenotypes are known to be under strong genetic regulation [3,4] . In the past decade, a number of candidate genes have been identified that may contribute to bone mineral density (BMD), but far less is known about genes affecting obesity phenotypes such as lean mass and fat mass [5,6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation